Structural integrity of the PCI domain of eIF3a/TIF32 is required for mRNA recruitment to the 43S pre-initiation complexes - Khoshnevis, Sohail; Gunišová, Stanislava; Vlčková, Vladislava; Kouba, Tomáš; Neumann, Piotr; Beznosková, Petra; Ficner, Ralf; Valášek, Leoš Shivaya (Nucleic acids research, 2014)
Transfer of genetic information from genes into proteins is mediated by messenger RNA (mRNA) that must be first recruited to ribosomal pre-initiation complexes (PICs) by a mechanism that is still poorly understood. Recent studies showed that besides eIF4F and poly(A)-binding protein, eIF3 also plays a critical role in this process, yet the molecular mechanism of its action is unknown. We showed previously that the PCI domain of the eIF3c/NIP1 subunit of yeast eIF3 is involved in RNA binding. To assess the role of the second PCI domain of eIF3 present in eIF3a/TIF32, we performed its mutational analysis and identified a 10-Ala-substitution (Box37) that severely reduces amounts of model mRNA in the 43-48S PICs in vivo as the major, if not the only, detectable defect. Crystal structure analysis of the a/TIF32-PCI domain at 2.65-Å resolution showed that it is required for integrity of the eIF3 core and, similarly to the c/NIP1-PCI, is capable of RNA binding. The putative RNA-binding surface defined by positively charged areas contains two Box37 residues, R363 and K364. Their substitutions with alanines severely impair the mRNA recruitment step in vivo suggesting that a/TIF32-PCI represents one of the key domains ensuring stable and efficient mRNA delivery to the PICs.
Keywords: transkripční faktory bZIP; Basic-Leucine Zipper Transcription Factors; iniciace translace peptidového řetězce; Models, Molecular; malé podjednotky ribozomu eukaryotické; Ribosome Subunits, Small, Eukaryotic; Mutation; Phenotype; Alanine; Saccharomyces cerevisiae Proteins; Amino Acid Substitution; Eukaryotic Initiation Factor-3; Protein Structure, Tertiary; RNA, Messenger; terciární struktura proteinů; eukaryotický iniciační faktor 3; alanin; mutace; molekulární modely; substituce aminokyselin; Saccharomyces cerevisiae - proteiny; fenotyp; Peptide Chain Initiation, Translational; messenger RNA